Analysis of the Influence of Personal Selling Media Promotion on Purchasing Decisions for MSMEs in Badung District (Case Study at Studio Umah Trisna, Jimbaran) - Jelita, Novita; Ayu, Sudha Sucandrawati Ni Luh Ketut; Gede, Supraptha I Nyoman (International Journal of Management and Business Intelligence, 2024)
This research aims to determine the influence of personal selling promotions via social media Instagram, TikTok, and Facebook partially and simultaneously on purchasing decisions among MSMEs in Badung Regency (Case Study at Studio Umah Trisna). Ninety clients who use Umah Trisna studio services are the subjects of this research. The sampling method uses the census method. This research uses a quantitative approach, and the data sources are primary and secondary. Data was collected through questionnaires. SPSS version 27.0 was used to process the collected data. Analysis was carried out using multiple linear regression, coefficient of determination, and hypothesis testing.  The results of data analysis show that the social media variables Instagram, Facebook, TikTok, and research have a positive and significant effect on purchasing decisions for Studio Umah Trisna Jimbaran MSMEs partially and simultaneously. The implication of this research is that this research found an analysis of the influence of personal selling media promotion on purchasing decisions among MSMEs in Badung Regency.